Obstructed Labour as Seen in Umuahia; Southeast Nigeria - Odusolu, Patience O.; Nkwo, Emeka C.; Nkwo, Glory C. E. (British Journal of Healthcare and Medical Research, 2022)
Background: Obstructed labour is one of the leading causes of maternal mortality accounting for 8% of maternal deaths globally and consuming scare resources budgeted for healthcare in Nigeria and Sub-Saharan Africa. Materials and Methods: This was a retrospective study carried out at the department of obstetrics and gynecology, Federal Medical Center Umuahia, Southeast Nigeria. The folders of all women who were diagnosed with obstructed labor in a 10-year period between January 2006 and December 2015 were retrieved and data extracted. The data was analyzed using proportions, frequencies, and percentages. Objective: To evaluate the sociodemographic profile, causes and feto - maternal outcomes of obstructed labor at the Federal Medical Center Umuahia. Results: The incidence of obstructed labor was 2.2%. Most of the women (93.7%) were between 20 and 39 years of age, (58.2%) were nulliparous while. Majority (61.1%) had secondary education though (93.7%) of the patients were unbooked. The commonest cause was cephalopelvic disproportion (61.2%) followed by malpresentation (30.5%). Commonest mode of delivery was emergency caesarean section (90.0%) and the least was symphysiotomy 3(1.2%). Hysterectomy 10 (4.2%) or uterine repair 11(4.6%) with or without bilateral tubal ligation were done for those with uterine rupture. The most frequent maternal complication was puerperal sepsis (26.2%) and there were 3(1.3%) maternal deaths. Majority (72.4%) of the babies were live births while 27.6% were stillbirths. Conclusion: Over ninety percent of the cases of obstructed labor were unbooked in this study. There is a need for education on the importance of antenatal care and skilled supervision during labor.